Pediculosis capitis in Elementary School Children in Kupang Regency - Michael Bhadi Bia; Aldiana Astuti; Lidia Vartika Putri; Noldiana Rini Hello; Junita Mogu Wole (Poltekkes Kemenkes Kupang, 2025)
Pediculosis capitis is a parasitic infestation caused by the head louse, Pediculus humanus capitis (PHC). These lice feed on human blood on the head. Head lice infestations most commonly occur among preschool and primary school children, as well as household members and caregivers. This study was conducted to provide an overview of the evidence regarding the prevalence of Pediculosis capitis among primary school students in Kupang Regency, East Nusa Tenggara. This study aimed to determine the prevalence of Pediculosis capitis and identify risk factors influencing its occurrence among primary school students in Kupang Regency. The study was conducted in primary schools in Kupang Regency during the 2023-2024 academic year. To identify cases of pediculosis, the presence of eggs/nymphs/adult Pediculus humanus capitis was detected using a lice comb. Clinical symptoms and signs were collected through interviews using a questionnaire and direct observation of clinical signs. A total of 278 children participated in the study, consisting of 164 boys (59%) and 114 girls (41%). Pediculosis cases were found in 151 children (54,3%). Characteristics of children influencing the occurrence of pediculosis include hair length and the number of family members living in the same household. Reported symptoms associated with pediculosis cases included dandruff, scalp itching, redness, difficulty sleeping, and poor concentration. Behaviours of primary school children related to the transmission of pediculosis include sleeping with an infected person, sharing hats, sharing combs at home, frequency of using a lice comb, and frequency of washing hair per week.